(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the principles, goals, and significance of interdisciplinary teaching in the context of school physics education. It presents a methodological framework for integrating interdisciplinary connections into the Grade 7 physics curriculum and offers practical recommendations for educators.